Enhanced photocatalytic performance of visible-light-driven BiOBr/BiPO4composites - Wachiraporn Maisang (2018)
© 2017 Elsevier Ltd. Photocatalytic activity of BiPO4was successfully improved by loading with different contents of BiOBr. The as-synthesized products were characterized by X-ray powder diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), Fourier transform infrared (FTIR) spectroscopy, Raman spectrophotometry, ultraviolet (UV)-visible spectroscopy and photoluminescence (PL) spectroscopy. The analytical results certified that the pure products were hexagonal BiPO4with rice-grain-like particles, tetragonal BiOBr with flower-like particles, and mixed phases and morphologies of the two individual constituents. Electrochemical impedance spectroscopy (EIS) and photocatalysis were evaluated and found that 50mol% BiOBr/BiPO4was the best composites for wastewater treatment.